Eleventh month, eleventh day, eleventh hour Armistice Day, 1918, World War I and its violent climax - Persico, Joseph E. (Random House Trade Paperbacks, 2005)
November 11, 1918. The final hours pulsate with tension as every man in the trenches hopes to escape the melancholy distinction of being the last to die in World War I. The Allied generals knew the fighting would end precisely at 11:00 A.M, yet in the final hours they flung men against an already beaten Germany. The result? Eleven thousand casualties suffered-more than during the D-Day invasion of Normandy. Why? Allied commanders wanted to punish the enemy to the very last moment and career officers saw a fast-fading chance for glory and promotion.